2007
DOI: 10.1016/j.jacc.2007.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Platelet Aggregation by AZD6140, A Reversible Oral P2Y12Receptor Antagonist, Compared With Clopidogrel in Patients With Acute Coronary Syndromes

Abstract: AZD6140 exhibited greater mean inhibition of platelet aggregation than a standard regimen of clopidogrel in ACS patients. In addition, AZD6140 further suppressed platelet aggregation in clopidogrel pretreated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
305
0
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(342 citation statements)
references
References 14 publications
19
305
0
18
Order By: Relevance
“…The differences in baseline characteristics were somewhat unexpected, as the drugs do not greatly differ from each other in terms of platelet inhibition. With the current approved maintenance dosing for both drugs, adequate levels of platelet inhibition 18 are achieved in over 90% of patients 11, 17, 19, 20, 21, 22.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in baseline characteristics were somewhat unexpected, as the drugs do not greatly differ from each other in terms of platelet inhibition. With the current approved maintenance dosing for both drugs, adequate levels of platelet inhibition 18 are achieved in over 90% of patients 11, 17, 19, 20, 21, 22.…”
Section: Discussionmentioning
confidence: 99%
“…17/39 (44%) and 19/37 (51%) of patients in the twice-daily 100 and 200 mg ticagrelor groups, respectively16. In patients with ACS, a similar 277% increase in ticagrelor exposure at week 4 was reported in those receiving 180 mg ticagrelor twice daily compared with 90 mg twice daily (mean AUC ± SD, 90 mg twice daily: 4762 ± 2443 ng·h/mL; 180 mg twice daily: 13,198 ± 4982 ng·h/mL), which was associated with a dose-dependent increase in IPA17. Total bleeding events in these patients with ACS were comparable between the two treatment groups: number of events (Kaplan–Meier event rates) 90 mg twice daily: 32 (9.8) and 180 mg twice daily: 25 (8.0) through week 4; and 90 mg twice daily: 34 (10.9) and 180 mg twice daily: 33 (11.4) through week 1231.…”
Section: Discussionmentioning
confidence: 73%
“…It is an orally active drug that binds reversibly to P2Y 12 , with a stronger and more rapid anti-platelet effect than clopidogrel. 21,22 The PLATO study showed that as compared to clopidogrel, ticagrelor was associated with a 16% relative risk reduction with regard to the primary end point-a composite of death from cardiovascular causes, myocardial infarction and stroke-but no significant increase in the overall risk of major bleeding. 23 The recommended dose is 180-mg loading dose, then 90 mg twice daily.…”
Section: Ticagrelormentioning
confidence: 99%